Countries And The Minerals Industry - NEFE NONE (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Possible New U.S. Half-Dollar. - Tile George Washington Commemorative Coin Act, H.R. 3133, was introduced in the House and approved by the House Banking Committee. It would allow the minting of at least 10 million commemorative silver half-dollars the size of the same coin produced before 1965. A companion bill, S. 1228, was introduced in the Senate. Taxes and the U.S. Minerals Industry. - The General Accounting Office completed a report to Congress on "Assessing the Impact of Federal and State Taxes On the Domestic Minerals Industry." the study presents a quantitative method to assess the effect of taxes on profitability, and suggests ways to use taxes or tax credits to help marginal mine operations and possibly to increase mineral production, Limited copies of the 139-page report are available free of charge from U.S. General Accounting Office, Documents Handling & Information Sevices Facility, P.O. Box 6015 Gaithersburg, Md. 20760.